The success factors of public private partnership: a literature review / Lydia Natalia and Ersa Tri Wahyuni - Natalia, Lydia; Wahyuni, Ersa Tri (Faculty of Accountancy, 2018)
Infrastructure, such as roads and airports, is one of the important factor in the economic growth, particularly for developing countries. However, several countries have limited funding to support their infrastructure development, this condition has therefore encourage governments to collaborate with private sectors in PPP (Public Private Partnership) scheme. The success stories of PPP that has been sampled in European, African and Asian Countries drive us to study the critical success factors of such partnerships. This study aims to analyze the critical success factors of PPP projects listed in the previous literature. The study assessed 20 published papers collected from Google Scholars and identify 60 critical success factors of PPP projects. The top five factors are: 1. Appropriate Risk Allocation, 2 Financial Market Availability, 3. Strong Private Consortium, 4. Opportune Relationship between Private and Public Parties, and 5. Competitive and Transparant Procurement Process. All those factors can be applied to any PPP projects and may assist the PPP stakeholders in increasing the probability on the success of their projects.